'At variance with the most elementary principles': the state of British colonial lunatic asylums in 1863. Issue 2 (June 2015) - Brunton, Warwick
In 1863 the Colonial Office reviewed colonial hospitals and lunatic asylums in those parts of the British Empire it administered – probably the first and widest international comparative study up to that date. This article outlines the background, process and scope of the review of asylums, and considers its significance. The resulting 'digest' is an important source to explain how, why, when and by whom metropolitan ideas acquired official endorsement and spread throughout the British world. Using the review's general findings and suggestions, a tool is provided for comparing inter-colonial achievements. With New Zealand as a case study, the article concludes that, relative to other influences, the digest played a limited and largely indirect part in shaping New Zealand's mental health policy before 1876.